Determination of Potential of Aquifer Contamination in the Municipality of Artur Nogueira (São Paulo, Brasil), Through Geoenvironmental Attributes - Ruggiero, Mayara Herrmann; Bentos, Adriel Barboza; Paganeli, Bruno; Adorno, Henrique Aio; Lorandi, Reinaldo; Di Lollo, José Augusto [UNESP]; Moschini, Luiz Eduardo (Universidad Nacional de Colombia, 2022)
Human activities exert constant pressures on groundwater. In fact, one of the most relevant problems is the anthropogenic addition of contaminants and pollutants, closely related with the land use. Analyzing the response of geoenvironmental factors associated to land use and occupation is an essential tool to identify how prone to contamination an aquifer is it, also widely used for territorial planning. Thus, the present study aimed to determine the aquifer contamination potential in Artur Nogueira city (São Paulo, Brasil). To do so, we used study area attributes related to the geology and geomorphology (aquifer units, unconsolidated materials, and slope), including soil use and occupation features. By using multi-criteria analysis and map algebra, this region exhibited a huge range of contamination potential. Our results showed that approximately 47 % of the city area displayed a medium potential. The highest one covered approximately 24 % of the study site. The large agricultural and livestock matrix in the region contributed strongly to those results. Another important factor was the physical environmental characteristics. This highlights how a planning lack regarding the land use and occupation directly influenced the groundwater contamination potential.
Determinación del potencial de contaminación de acuíferos en el municipio de Artur Nogueira (São Paulo, Brasil), a través de atributos geoambientales
Determinação do potencial de contaminação de aquíferos no município de Artur Nogueira (São Paulo, Brasil), por meio de atributos geoambientais
Keywords: Geographic Information System; geographical data; groundwater; land use; pollution